Property mananagement and real estate investing - how to build and nurture portfolio for private investor - Lenc, Aleš; Smrčka, Luboš; Schönfeld, Jaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This paper will be focused on real estate investments and its management. This work aims to describe all aspects of residential property management. Since the vast majority of literature about property management is written based on legal the environment of USA or other Anglo-Saxon countries, the aim will be the to transfer the best practices from the literature to legal environment of the Czech Republic. Further aim is to provide reader with complete knowledge about residential property management including suggestions for more efficient and less time-consuming work.
Vedoucí práce: Luboš Smrčka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses